The Influence Of Transformational Leadership Style And Work Motivation On Teacher Performance Mediated By Work Discipline On Teachers Of MTs Al-Fathimiyah Karawang - Ai Revi Resmiati; Supriyanto Supriyanto; Taufiq Rachman (UNIVED Press, 2024)
This study aims to determine The Influence Of Transformational Leadership Style And Work Motivation On Teacher Performance Mediated By Work Discipline On Teachers Of Mts Al-Fathimiyah Karawang. Respondents of this study were 30 respondents and this study used a quantitative approach with the SmartPLS 3.0 data processing application. The results of this study found that 1. Transformational Leadership Style has no effect on Teacher Performance, 2. Work Motivation has a positive and significant effect on Teacher Performance, 3. Discipline has a positive and significant effect on Teacher Performance, 4. Transformational Leadership style has a positive and significant effect on Discipline, 5. Work Motivation has no effect on Discipline, 6. Transformational Leadership Style has a positive and significant effect on Work Performance mediated by Discipline, 7. Work Motivation has no effect on Work Performance mediated by Discipline.